An analysis of the Indian Economy during the three COVID-19 pandemic waves - Baber, Hasnan; Shaik, Muneer; Gupta, Himani (Technological and Economic Development of Economy, 2025)
The objective of the study was to examine the effects of the COVID-19 pandemic on India’s economy. The analysis focused on several economic metrics, including stock market prices, the rupee’s value in relation to the US dollar, economic activity, the unemployment rate, and the rate of inflation. Contrary to popular belief, the results demonstrate that during the first wave (25 March 2020 to 16 September 2020), the increasing number of cases had a beneficial influence on economic activity and a negative impact on the unemployment rate. The second wave, which lasted from 15 March 2021 to 17 July 2021, was considerably stronger and demonstrated how confirmed instances had a significant detrimental impact on inflation rates and stock values. Contrary to expectations, the third wave (December 28, 2021, to January 30, 2022) was found to be less intense. Overall, the report shows how the pandemic affected India’s economy during each of the three waves and notes that there have been encouraging signs of recovery during the return to normalcy phase. The government, scholars, policymakers, and economists will find this study useful in understanding how the COVID-19 Pandemic affected the Indian economy and in coming up with ideas for future risk mitigation measures.First published online 26 August 2024